2019
DOI: 10.1038/s41467-019-11591-1
|View full text |Cite|
|
Sign up to set email alerts
|

A general approach for detecting expressed mutations in AML cells using single cell RNA-sequencing

Abstract: Virtually all tumors are genetically heterogeneous, containing mutationally-defined subclonal cell populations that often have distinct phenotypes. Single-cell RNA-sequencing has revealed that a variety of tumors are also transcriptionally heterogeneous, but the relationship between expression heterogeneity and subclonal architecture is unclear. Here, we address this question in the context of Acute Myeloid Leukemia (AML) by integrating whole genome sequencing with single-cell RNA-sequencing (using the 10x Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
174
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(179 citation statements)
references
References 73 publications
5
174
0
Order By: Relevance
“…Recent single cell RNA-sequencing work has demonstrated that leukemia can exist along a continuum of differentiation states and as such, we sought to determine if the genetic clonal architecture we identified above was associated with particular differentiation states 20,21 . We performed simultaneous single cell DNA molecular profiling and cell surface protein expression analysis on AML samples (n = 17) using a DNA + protein single cell sequencing adaptation of the Tapestri platform.…”
Section: Resultsmentioning
confidence: 99%
“…Recent single cell RNA-sequencing work has demonstrated that leukemia can exist along a continuum of differentiation states and as such, we sought to determine if the genetic clonal architecture we identified above was associated with particular differentiation states 20,21 . We performed simultaneous single cell DNA molecular profiling and cell surface protein expression analysis on AML samples (n = 17) using a DNA + protein single cell sequencing adaptation of the Tapestri platform.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate that HLA genes present cell-type specific expression (Boegel et al 2018) and that HLA loss of expression can be evaluated per-cell and per-cluster. Using five AML samples published in (Petti et al 2019) for which HLA class I and class II genotypes were provided by the authors, we demonstrate the ability to find cell type specific allele bias when cell types have been annotated using marker genes. We also analyze data from two Merkel cell carcinoma (MCC) patients published in (Yost et al 2019) and extend their finding that HLA class I expression is lost, to show that this expression loss may be allele-specific.…”
Section: Resultsmentioning
confidence: 99%
“…10x Genomics Chromium 5’ GEX library data derived from five subjects with AML, as described in (Petti et al 2019) was reanalyzed. Genotypes for HLA-A, -B, -C, -DRB1, and -DQB1 at two-field resolution were provided by the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given recent reports of using 10× Genomics single-cell RNA-seq data for calling variants within genes and nearby regions, 25 we next examined the overall distribution of variants in the ASD and control samples. For this purpose, we carried out variant calling at bulk level (see "Methods"), obtaining a list of variants present in each genomic region.…”
Section: Snv Analysismentioning
confidence: 99%